The role of state intervention in the financial sector: Crisis prevention, containment, and resolution - Yoon Je Cho (Asian Development Bank Institute (ADBI), 2010)
This paper discusses the role of state intervention for prevention, containment, and resolution of financial crises based mainly on the Korean experience during the 1997 Asian financial crisis. Crises in emerging market and developing economies tend to be more complicated than those faced by advanced economies because they are twin crises: financial and currency crises. Such crises require the development of a comprehensive strategy covering the stabilization of the domestic financial market and the foreign exchange market, closely coordinated responses by different government bodies, an extraordinary effort for financial restructuring, and the introduction of a new regulatory framework. This effort should be based on an effective crisis management team of experts given a clear mandate with well defined power; strong political support; effective communication with the market players, both domestic and foreign; and sufficient mobilization of public funds. In this regard, this paper emphasizes the importance of building a reliable information base, prompt actions, orchestrating political consensus, and a balanced approach to restructuring and regulation among different types of financial institutions. The paper also highlights the need for a new international financial architecture matching the rapid integration into the global market of the financial markets of emerging and developing economies while their currency remains non-convertible.
Keywords: E58; G01; G18; G21; G28; F34; F36; N20; O16; 330; Finanzmarktkrise; Kapitalmarktliberalisierung; Regulierung; Finanzsektor; Wirkungsanalyse; Asien